Assimilation experienced by quang ngai students in pham van dong university - problems and solutions (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study paper investigated how assimilation is experienced by students of English at Pham Van Dong University, Quang Ngai province, Viet Nam. The thesis explored the difficulties of students on perception and production in terms of assimilation when communicating in casual and rapid speech. The major differences between Vietnamese and English Phonetic System and the failure of ending sound pronunciation were set out for the hypotheses of the study. Dropping ending sounds or enunciation was likely to cause the difficulties for the Vietnamese students in performing assimilation in casual and natural communication in English. A questionnaire to collect data of students’ attitude on language skills in general and on pronunciation concerning assimilation in particular was administered to Quang Ngai 1st, 2nd and 3rd year students of English. A diagnostic test of how students perceived and produced assimilated sequences of sounds at phrase and sentence levels was designed to test the hypotheses of student experiences in the perception and production in natural and fast speech. The short- term target of the study is to investigate and provide solutions to the problems that the students may encounter assimilation in a sound sequence when communicating in oral channel. Moreover, enunciation in slow speech and the influence of the mother tongue hindered students from fluency and being incapable of producing assimilation in natural and fast speech are the results of my research findings and effectively recommended solutions intended to contribute to the process of teaching and learning English as far as verbal communication is concerned.